Selective Metaphor Impairments After Left, Not Right, Hemisphere Injury - Cardillo, Eileen R.; McQuire, Marguerite; Chatterjee, Anjan (Frontiers in Psychology, 2018)
The relative contributions of the left and right hemispheres to the processing of metaphoric language remains unresolved. Neuropsychological studies of brain-injured patients have motivated the hypothesis that the right hemisphere plays a critical role in understanding metaphors. However, the data are inconsistent and the hypothesis is not well-supported by neuroimaging research. To address this ambiguity about the right hemisphere’s role, we administered a metaphor sentence comprehension task to 20 left-hemisphere injured patients, 20 right hemisphere injured patients, and 20 healthy controls. Stimuli consisted of metaphors of three different types: predicate metaphors based on action verbs, nominal metaphors based on event nouns, and nominal metaphors based on entity nouns. For each metaphor (n = 60), a closely matched literal sentence with the same source term was also generated. Each sentence was followed by four adjective-noun answer choices (target + three foil types) and participants were instructed to select the phrase that best matched the meaning of the sentence. As a group, both left and right hemisphere patients performed worse on metaphoric than literal sentences, and the degree of this difficulty varied for the different types of metaphor – but there was no difference between the two patient groups. Tests for literal-metaphor dissociations at the level of single cases revealed two types of impairments: general comprehension deficits affecting metaphors and literal sentences equally, and selective metaphor impairments that were specific to different types of metaphor. All cases with selective metaphor deficits had injury to the left hemisphere, and no known comprehension difficulties with literal language. Our results argue against the hypothesis of a specific or necessary contribution of the right hemisphere for understanding metaphoric language. Further, they reveal deficits in metaphoric language comprehension not captured by traditional language assessments, suggesting overlooked communication difficulties in left hemisphere patients.